Educational leadership from a philosophical and Islamic perspective - Muhammad Nasri Dini (IAIN Salatiga, 2020)
AbstractAn educational leader must comprehend educational leadership theory to perform good leadership. A lot of educational practitioners have not understood yet. What does educational leadership mean? How does philosophical and Islamic view see educational leadership? This research aims at explaining them to society mainly for those who contribute to Islamic institutions by applying a library research approach, moreover for the source of data the author takes documentation in form of a notebook, journal article, and other written data or documents. Based on the philosophical view, educational leadership shall suit ontology, epistemology, and axiology theories. The varieties of philosophical leadership are coming from Plato, Aristoteles, and Machiavelli. While in the Islamic view, the leader requires to have prophet Muhammad's characters, for instance: sidiq/honest; amanah/trustworthy; tabligh/communicative; and fathonah/intelligent.